Field Evaluation of Integrated Pest Management Strategies against Chilli Black Thrips Thrips parvispinus (Karny), in the Srikakulam District - Anusha, S.; Kumar, V Hari; Kumar, S Kiran; Neelaveni, S; Suneetha, B; Krishna, Ch Bala; Lakshmi, K Bhagya (UTTAR PRADESH JOURNAL OF ZOOLOGY, 2024)
Chilli (Capsicum annum L) is an important spice crop grown extensively in India for both domestic and export markets. Invasive black thrips Thrips parvispinus has been causing destructive damage to chilli crop in India leading to indiscriminate use of insecticidal sprays. On-farm trials were conducted during Kharif and Rabi 2022-23 & 2023-24 to evaluate Integrated Pest Management practices against black thrips with emphasis on minimal pesticidal sprays with different mode of actions so that pests may not develop resistance which will reduce the residues on the produce in the farmer’s fields of Srikakulam district of Andhra Pradesh. IPM adopted fields i.e. seed treatment, marigold as trap crop, erection of blue sticky traps, Beauveria bassiana spray and Neem oil and Fipronil 5 SC spray at 30 DAT; Imidacloprid+Fipronil 40%WG spray at 50 DAT; have shown 40 to 85 per cent reduction in black thrips infestation over farmers practice during all the seasons of both the years. This resulted in a higher average mean yield of 57 q/ha, average net returns of Rs. 4,96,000 per hectare with cost benefit ratio of 3.29 in IPM fields over farmer’s practice depicting that the adoption of IPM practices helped in reducing the pest incidence and increase in yield, net returns.